Millimeter-Wave Microstrip Antenna Array Design and an Adaptive Algorithm for Future 5G Wireless Communication Systems - Cheng-Nan Hu; Dau-Chyrh Chang; Chung-Hang Yu; Tsai-Wen Hsaio; Der-Phone Lin (International Journal of Antennas and Propagation)
This paper presents a high gain millimeter-wave (mmW) low-temperature cofired ceramic (LTCC) microstrip antenna array with a compact, simple, and low-profile structure. Incorporating minimum mean square error (MMSE) adaptive algorithms with the proposed 64-element microstrip antenna array, the numerical investigation reveals substantial improvements in interference reduction. A prototype is presented with a simple design for mass production. As an experiment, HFSS was used to simulate an antenna with a width of 1 mm and a length of 1.23 mm, resonating at 38 GHz. Two identical mmW LTCC microstrip antenna arrays were built for measurement, and the center element was excited. The results demonstrated a return loss better than 15 dB and a peak gain higher than 6.5 dBi at frequencies of interest, which verified the feasibility of the design concept.